2016
DOI: 10.18671/scifor.v44n109.11
|View full text |Cite
|
Sign up to set email alerts
|

Testes de identidade de modelos aplicados na construção de curvas de índices de local e na produção de povoamentos de Eucalyptus grandis

Abstract: ResumoEste trabalho teve como objetivo aplicar testes de identidade de modelos na construção de curvas de índi-ces de local e na produção da área basal e do volume por hectare em povoamentos de Eucalyptus grandis W. Hill. Ex. Maiden para seis fazendas de uma região do estado de São Paulo. O teste de Regazzi (2003) foi aplicado para analisar a possibilidade de utilização de um único modelo de altura dominante para todas as fazendas. A curva média de produção em área basal e volume ajustada pelo modelo de Clutte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This indicates that the trees whose understory was grazed could not express their peak growth potential. The factors that lead to the anticipation of the technical harvesting age are associated with the productive capacity of the site, given the changes that can occur in a stand, the type of soil, species, genetic material, water and nutrient availability, spacing, light and temperature, production costs, the market for timber and by-products, fires, damage caused by pests and diseases or natural events (Roveda;Dias;Figueiredo Filho;Scavinski;Castro, 2016), and, as seen in this study, damage caused by animals in integration systems when they are not released at the right time.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the trees whose understory was grazed could not express their peak growth potential. The factors that lead to the anticipation of the technical harvesting age are associated with the productive capacity of the site, given the changes that can occur in a stand, the type of soil, species, genetic material, water and nutrient availability, spacing, light and temperature, production costs, the market for timber and by-products, fires, damage caused by pests and diseases or natural events (Roveda;Dias;Figueiredo Filho;Scavinski;Castro, 2016), and, as seen in this study, damage caused by animals in integration systems when they are not released at the right time.…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 2 (b), considering only layer 2 in relation to the two management systems (T and Sg), it was observed that the regression distances resulted in overlapping confidence intervals only at the ends of the equation where the experimental error is larger, indicating that there is a difference between the regressions in this soil layer. Roveda et al (2016) evaluated eucalyptus growth in six different locations, and observed that two models did not show statistical difference through the Model Identity method, indicating the possibility of using a single plant growth curve for these locations. For the others, as there was a statistical difference, it was concluded by using a specific model for each location.…”
Section: Borges I B Et Al 525mentioning
confidence: 99%
“…Variations in exploitation form and depth of the root system of plants used in covers and their capacity of biomass production, in relation to the main crop, allow the recycling of nutrients, several models are observed. This procedure has been widely used in forestry engineering due to the large number of models generated for administrative planning and prediction of yield capacity and production (ROVEDA et al, 2016). Thus, this procedure could be used in the comparison of models that describe the behavior of the calibration of a neutron probe under different types of soil and / or handling.…”
Section: Introductionmentioning
confidence: 99%